Diffuse alveolar hemorrhage induced by inhaled Sevoflurane. Case report and literature review - Jaime H. Jordan; Santiago Pedroza; Einar S. Billefals; Gustavo Cruz (Respiratory Medicine Case Reports, 2023)
Diffuse alveolar hemorrhage secondary to sevoflurane inhalation is a rare condition. It should be considered in postoperative patients presenting symptoms of hemoptysis, hypoxemia, or radiographic alveolar infiltrates. We present the case of a 42-year-old man who experienced a diffuse alveolar hemorrhage following sedation with sevoflurane during a low-risk orthopedic procedure. Initially, the patient presented hemoptysis, hypoxemia, and dyspnea. X-ray findings suggested alveolar hemorrhage and the diagnosis was confirmed with fiberoptic bronchoscopy. The patient improved under the care of the pulmonary service and was discharged. Early identification and management of this respiratory complication were crucial for a successful recovery.